THE ROLE AND CONSIDERATION OF PERSONAL FACTORS IN THE PROCESS OF TEACHING A FOREIGN LANGUAGE TO STUDENTS AT A NON-PHILOLOGICAL UNIVERSITY - Turaeva Shahida Egamberdievna (Western European Studies, 2024)
The article discusses the awareness of the need to speak at least one foreign language. The low efficiency of mastering a foreign language by students of non-linguistic faculties of universities is largely due to completely objective reasons that do not depend on teachers. In this regard, there is a need to explore possible ways to improve the educational process in relation to a non-linguistic university, since it is precisely the issues of increasing the efficiency of mastering a foreign language in the real existing conditions of a given university that require additional attention
Keywords: overcrowding of groups; determining role; according to the psychological nature